The impact of Artificial Intelligence (AI) on employment / Anis Suriana Sainuddin ... [et al.] - Sainuddin, Anis Suriana; Harman, Muhammad Haziq; Mohamad Nawawi, Nur Fadhlin Sakina; Muhamad Fauzi, Nur Arifah Alia; Othman, Puteri Nur Chempaka Ellyssya; Ali, Asiah (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
Artificial Intelligence (AI) is revolutionizing industries worldwide, significantly affecting the job market. While AI enhances efficiency, productivity, and innovation, it also presents employment challenges, particularly concerning job displacement and the transformation of traditional roles. This report examines AI's impact on employment, highlighting both the positive and negative effects while suggesting strategies to adapt to these changes.